Development of tissue-inspired scaffolds : integrating biology with materials science - Luo, Baiwen (2015)
The lack of a definitive strategy for soft tissue regeneration highlights the need to evaluate new approaches for soft tissue replacement that is of clinical relevance. As tissue engineering presents a promising strategy for soft tissue regeneration, the focus of this thesis is mainly on the development of tissue-inspired scaffolds for adipose tissue engineering applications. In order to achieve this objective, studies were carried out to evaluate the efficacy of two novel materials, namely adipose tissue-derived extracellular matrix (ECM) material and bullfrog skin-derived collagen. Taking inspiration from the native tissue itself, decellularized tissue-derived ECM is regarded as a promising material for tissue engineering applications. However, it has been shown that different decellularization methods play an influential role over the property of the final decellularized ECM material. Two novel decellularization methods were established during the course of this thesis for the isolation of ECM material from adipose tissue without the need of any harsh chemicals. The ECM material isolated using these two methods led to the preservation of more biological components including growth factors, matricellular proteins and structural proteins, as compared to previously established decellularization methods. The extracted ECM material was subsequently used as a bioactive material to enrich other biomaterials for tissue engineering applications for the first time. It was found that the ECM material was an effective enrichment due to the well preservation of various valuable components within ECM material. This ECM enrichment improved the cell-material interaction for both synthetic (i.e. Polycaprolactone) and natural (i.e. Ovalbumin) materials. In addition, the ECM coating was observed to have minimal pro-inflammatory response and improved in vitro wound healing, endothelialization, and adipogenesis. In parallel, in vitro and in vivo studies were also carried out to demonstrate how bullfrog skin-derived collagen could be a promising alternative source of collagen for the fabrication of tunable acid-soluble collagen (AC) scaffolds. The material properties and cell proliferation capabilities of the AC scaffolds could be further modulated using different concentrations of crosslinker to suit various tissue engineering applications. In addition, a decrease in both in vitro and in vivo degradation rate was observed with increasing crosslinker concentration. Overall, by combining engineering tools and techniques with biological assays and animal studies, adipose tissue-derived ECM material and bullfrog skin-derived collagen were shown to be promising materials for soft tissue engineering applications. The novel concept of using ECM material to improve cell–material interactions demonstrates the potential exploitation of adipose tissue as useful bioactive coating material. Overall, an ECM-containing hybrid scaffold is an acellular scaffold with cellular benefits and is therefore a great stepping-stone towards the development of engineered adipose tissue replacement for clinical applications.